2020
DOI: 10.1111/jeb.13673
|View full text |Cite
|
Sign up to set email alerts
|

Female sperm storage mediates post‐copulatory costs and benefits of ejaculate anticipatory plasticity in the guppy

Abstract: Males of many species evolved the capability of adjusting their ejaculate phenotype in response to social cues to match the expected mating conditions. When females store sperm for a prolonged time, the expected fitness return of plastic adjustments of ejaculate phenotype may depend on the interval between mating and fertilization. Although prolonged female sperm storage (FSS) increases the opportunity for sperm competition, as a consequence of the longer temporal overlap of ejaculates from several males, it m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 108 publications
0
15
0
Order By: Relevance
“…2002; Kelly and Jennions 2011; Cattelan and Pilastro 2018; Cardozo et al. 2020) also indicates that ejaculates are a limited resource, consistent with their production being costly. However, we recently showed that male G. holbrooki have a lower risk of sperm depletion and do not adjust ejaculate components in response to social status or female cues (Chung et al.…”
Section: Discussionmentioning
confidence: 91%
“…2002; Kelly and Jennions 2011; Cattelan and Pilastro 2018; Cardozo et al. 2020) also indicates that ejaculates are a limited resource, consistent with their production being costly. However, we recently showed that male G. holbrooki have a lower risk of sperm depletion and do not adjust ejaculate components in response to social status or female cues (Chung et al.…”
Section: Discussionmentioning
confidence: 91%
“…Evidence of such a trade-off has been found in many species, e.g. 53 55 . As recently suggested by Reinhardt and Turnell 31 , this trade-off could be mediated by sperm metabolic rate.…”
Section: Discussionmentioning
confidence: 97%
“…On one hand, high mating opportunities may allow males to release sperm frequently, thus minimizing the need for the evolution of a strategy to avoid the consequences of long sperm storage. On the other hand, since under high mating availability and sperm competition (the competition between sperm from different males 65 ) males producing more sperm usually fertilize more eggs 66 , males may have been selected for continuously producing sperm to avoid sperm limitation even at the cost of sperm quality 55 . Moreover, it is worth noting that in our study we individually isolated males during sexual rest to avoid the confunding effects of social environment, which could have made difficult the interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
“…R. Soc. B 288: 20210979 other ejaculate traits, namely sperm morphology, sperm viability and seminal fluid content, must explain the higher fertilization success of older males [46,[56][57][58]. We recommend that future studies measure a greater range of ejaculate traits when testing for the effect of age and mating history on male reproductive senescence.…”
Section: (B) Sperm Velocitymentioning
confidence: 99%